Advances in chitosan-based microcapsules and their applications - Meng Q.; Zhong S.; Wang J.; Gao Y.; Cui X.
Microcapsules have attracted attention due to their widespread applications. Among the numerous wall materials of microcapsules, chitosan is a promising candidate due to its various merits, such as natural, nontoxic, biocompatible and biodegradable. Chitosan-based microcapsules have broad application scope and application prospects. Recently, chitosan-based microcapsules are used in biomedical and food science increasingly, which show the great practical application potential of chitosan microcapsules. This review discussed and analyzed the preparation methods and design strategies of chitosan-based microcapsules for various applications. And summarized the design considerations of the chitosan-based microcapsule in different applications for biomedical and food science. It is expected to provide researchers with inspiration and design ideas about chitosan-based microcapsules. © 2022
Keywords: BIOMEDICAL; CHITOSAN; FOOD SCIENCE; MICROCAPSULES